The geometry of the Sagittarius stream from Pan-STARRS1 3π RR Lyrae - Hernitschek, Nina; Rix, Hans-Walter; Martínez-Delgado, David (The astrophysical journal, 2017)
We present a comprehensive and precise description of the Sagittarius (Sgr) stellar stream’s 3D geometry as traced by its old stellar population. This analysis draws on the sample of ∼44,000 RR Lyrae (RRab) stars from the Pan-STARRS1 (PS1) 3 π survey, which is ##IMG## [http://ej.iop.org/images/0004-637X/850/1/96/apjaa960cieqn2.gif] $\sim 80 % $ complete and ##IMG## [http://ej.iop.org/images/0004-637X/850/1/96/apjaa960cieqn3.gif] $\sim 90 % $ pure within 80 kpc, and extends to ##IMG## [http://ej.iop.org/images/0004-637X/850/1/96/apjaa960cieqn4.gif] $\gtrsim 120\,\mathrmkpc$ with a distance precision of ##IMG## [http://ej.iop.org/images/0004-637X/850/1/96/apjaa960cieqn5.gif] $\sim 3 % $ . A projection of RR Lyrae stars within ##IMG## [http://ej.iop.org/images/0004-637X/850/1/96/apjaa960cieqn6.gif] $| \tildeB| _ødot \lt 9^° $ of the Sgr stream’s orbital plane reveals the morphology of both the leading and the trailing arms at very high contrast across much of the sky. In particular, the map traces the stream near-contiguously through the distant apocenters. We fit a simple model for the mean distance and line-of-sight depth of the Sgr stream as a function of the orbital plane angle ##IMG## [http://ej.iop.org/images/0004-637X/850/1/96/apjaa960cieqn7.gif] $\tilde\rmΛ _ødot $ , along with a power-law background model for the field stars. This modeling results in estimates of the mean stream distance precise to ##IMG## [http://ej.iop.org/images/0004-637X/850/1/96/apjaa960cieqn8.gif] $\sim 1 % $ and it resolves the stream’s line-of-sight depth. These improved geometric constraints can serve as new constraints for dynamical stream models.
Gesehen am 13.01.2021